Effects of Leymus Chinensis (Trin.) Tzvelev Grassland Litter Return on Soil Microbial Biomass Carbon of the Songnen Sandy Land in China - Zhao , Yujie; Du, Huishi (Bangladesh Journal of Botany, 2023)
Effects of litter return of Leymus chinensis grassland on soil microbial biomass carbon of the Songnen sandy land were investigated. Characteristics of soil microbial biomass carbon (SMBC) from subhumid area of L. chinensis grassland ecosystem at different content of litter returns (0, 200 and 400 g/m2) and soil depths (0-10, 10-20, 20-30 and 30-40 cm) were evaluated. Results showed that the content of SMBC increased with the increase in litter return at the same soil depth. The content was highest (426.17 mg/kg) at 400 g/m2 litter return, which was 1.61 and 1.50 times higher than at 0 and 200 g/m2, respectively at the depth of 0-10 cm, and decreased sharply at 10-40 cm. These results showed that increasing the amount of litter return and suitable management measures can effectively enhance the carbon content of soil microbial biomass and improve soil microbial activity and fertility to ensure the balance of grassland ecosystem. Bangladesh J. Bot. 51(4): 907-912, 2022 (December) Special